On Sylow subgroups of Shunkov periodic groups - Senashov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study the structure of Sylow 2-subgroups in Shunkov periodic groups with almost layer-finite normalizers of finite nontrivial subgroups.